Rheology, permeability and microstructure of seawater-based slurry for slurry shield tunneling: insights from laboratory tests - Ru, Junqi; Fang, Yingran; Guo, Yidong; Jiang, Luqing; Liu, Hongzhi; Li, Xinggao; Qi, Weiqiang (Frontiers in Materials, 2025)
During slurry shield tunneling in submarine geological conditions, it is of significance to prepare an appropriate slurry to maintain excellent rheological properties and penetration characteristics. To investigate the effects of seawater intrusion and high-temperature-induced deterioration on the physical properties of different bentonite slurries, four typical commercial sodium bentonites of different origins were selected as raw materials in this study, and mineral composition characterization tests were carried out on the four sodium bentonites, respectively. Additionally, a comprehensive analysis was performed to evaluate the physical properties of the four bentonite slurries, including rheological tests, penetration tests, and microstructure observations. The results indicated that both increased seawater content and elevated temperature had remarkable effects on the rheological properties of the slurries, while the rheological and permeability properties of all four slurries deteriorated to varying degrees. The microstructure and morphology of the slurries mainly appeared as thin sheets with voids between them, and discrete particle accumulation was observed locally. The conclusions presented in this paper could offer guidance for future preparation of slurries used in slurry shield tunneling.